2004
DOI: 10.1242/jeb.01263
|View full text |Cite
|
Sign up to set email alerts
|

Temperature and the expression of myogenic regulatory factors (MRFs) and myosin heavy chain isoforms during embryogenesis in the common carpCyprinus carpioL.

Abstract: 4239The myogenic regulatory factors (MRFs) are a family of basic helix-loop-helix (bHLH) transcription factors essential to the specification and determination of the muscle cell Supplementary material available online at

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
30
0
1

Year Published

2006
2006
2012
2012

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(36 citation statements)
references
References 81 publications
5
30
0
1
Order By: Relevance
“…Temperature has been shown to affect the sequence of organogenesis (Johnston et al, 1995), rate of somitogenesis (Brooks and Johnston, 1994) (present study), number of somites (Brooks and Johnston, 1994), number and size of muscle fibres at hatching (Vieira and Johnston, 1992;Brooks and Johnston, 1993;Usher et al, 1994;Nathanailides et al, 1995;Johnston and McLay, 1997;Alami-Durante et al, 1997;Galloway et al, 1998;Galloway et al, 1999; and the relative timing of myofibrillogenesis (Johnston et al, 1995) in different fish species. However, in agreement with our halibut study, relative temporal and spatial expression of several muscle genes in Atlantic herring Clupea harengus (Temple et al, 2001), Atlantic cod Gadus morhua and common carp Cyprinus carpio (Cole et al, 2004) do not seem to be influenced by temperature. Temple et al concluded (Temple et al, 2001) that temperature probably affects myofibril synthesis downstream from MyHC transcription, at the translation or assembly stage.…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations
“…Temperature has been shown to affect the sequence of organogenesis (Johnston et al, 1995), rate of somitogenesis (Brooks and Johnston, 1994) (present study), number of somites (Brooks and Johnston, 1994), number and size of muscle fibres at hatching (Vieira and Johnston, 1992;Brooks and Johnston, 1993;Usher et al, 1994;Nathanailides et al, 1995;Johnston and McLay, 1997;Alami-Durante et al, 1997;Galloway et al, 1998;Galloway et al, 1999; and the relative timing of myofibrillogenesis (Johnston et al, 1995) in different fish species. However, in agreement with our halibut study, relative temporal and spatial expression of several muscle genes in Atlantic herring Clupea harengus (Temple et al, 2001), Atlantic cod Gadus morhua and common carp Cyprinus carpio (Cole et al, 2004) do not seem to be influenced by temperature. Temple et al concluded (Temple et al, 2001) that temperature probably affects myofibril synthesis downstream from MyHC transcription, at the translation or assembly stage.…”
Section: Discussionsupporting
confidence: 91%
“…In most fish species where MyoD has been studied to date [zebrafish Danio rerio (Weinberg et al, 1996); Atlantic herring (Temple et al, 2001); gilthead seabream (Tan and Du, 2002); common carp (Cole et al, 2004); rainbow trout (Delalande and Rescan, 1999;Xie et al, 2001); flounder Paralichthys olivaceus (Zhang et al, 2006)], the gene is expressed in presomitic and somitic adaxial cells, which will later become the superficial slow red muscle fibres (Devoto et al, 1996). Subsequently, MyoD is expressed in lateral cells of the somites, which will form the bulk of the fast white muscle mass.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…These cold-specific isoforms have properties that increase performance in the cold, perhaps due to possession of a more flexible protein structure. Cold also causes significant changes to the expression of myogenic regulatory factors during embryogenesis and development (Cole et al, 2004) and following the restoration of warm conditions in cold-acclimated adult carp (Kobiyama et al, 2000). These might be important in specifying the different muscle phenotypes in the cold.…”
Section: Carp Muscle Responsesmentioning
confidence: 99%